LO78: A qualitative evaluation of a mandatory provincial program auditing emergency department return visits. (May 2019) - Jalali, H.; Ostrow, O.; Dainty, K.; Seaton, B.; Ovens, H.; Borgundvaag, B.; McLeod, S.; Chartier, L.
Abstract : Introduction : The Ontario emergency department (ED) Return Visit Quality Program (RVQP) launched in 2016 and aims to promote continuous quality improvement (QI) in the province's largest EDs. The program mandates routine audits of cases involving patients who had ED return visits within 72hrs that led to admission to hospital, in order to identify quality issues that can be tackled through QI initiatives. Our objective was to formally evaluate how well the RVQP achieved its aim of promoting continuous QI at participating sites using the constructivist grounded theory.Methods : Using a semi-structured interview guide, we employed a maximum variation sampling approach to ensure diverse representation across several geographical and institutional experiences (e.g., urban vs. rural, academic vs. community). Selected RVQP program leads were invited to participate in a phone interview to yield maximal insight, additionally using a snowball sampling approach to reach non-lead physicians to capture the penetration of the program. Interviews were conducted until thematic saturation was reached and no new insights were gleaned. Interviews were initially cross-performed by two members of the research team, recorded, transcribed, and de-identified. Data analysis was conducted using a constant comparative approach through the development of a coding framework and triangulation with the respondents' ED setting. We then grouped, compared and refined our analytic categories through an inductive, iterative approach.Results : Between June and August 2018, we interviewed 32 participants, including 21 RVQP program leads and 11 non-lead physicians, from a total of 23 diverse sites (out of 84). Our analysis suggests that the RVQP provides a structured method for EDs to frame the continuous collection of data in order to channel activities towards quality improvement projects based on identified needs. Success factors included: greater involvement with QI processes prior to the RVQP leading to more openness to improvement, a more collaborative approach to RVQP implementation which led to greater front-line workers' understanding and engagement, and more resources dedicated to implementing the RVQP as well as tackling the quality issues it identified.Conclusion : This study evaluated the impact of an innovative and large-scale program aimed at improving the culture of quality in Ontario EDs. While the program is still relatively new, early results show that there are key elements of EDs that support building a culture of QI.